2018
DOI: 10.1038/s41426-018-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

Replication and pathogenic potential of influenza A virus subtypes H3, H7, and H15 from free-range ducks in Bangladesh in mammals

Abstract: Surveillance of wild aquatic birds and free-range domestic ducks in the Tanguar Haor wetlands in Bangladesh has identified influenza virus subtypes H3N6, H7N1, H7N5, H7N9, and H15N9. Molecular characterization of these viruses indicates their contribution to the genesis of new genotypes of H5N1 influenza viruses from clade 2.3.2.1a that are dominant in poultry markets in Bangladesh as well as to the genesis of the highly pathogenic H5N8 virus currently causing disease outbreaks in domestic poultry in Europe an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Recently, we described the replication and pathogenic potential of H3, H7, and H15 viruses from free-range ducks in Bangladesh using mice. We observed that H7N1 and H7N9 viruses caused 100% and 60% mortality respectively, and expanded their tissue tropism beyond the pulmonary tissues to heart, liver, and brain 36 . Our current study showed this for both H10N1 and H10N6 AIVs as well as high mortality in mice.…”
Section: Discussionmentioning
confidence: 85%
“…Recently, we described the replication and pathogenic potential of H3, H7, and H15 viruses from free-range ducks in Bangladesh using mice. We observed that H7N1 and H7N9 viruses caused 100% and 60% mortality respectively, and expanded their tissue tropism beyond the pulmonary tissues to heart, liver, and brain 36 . Our current study showed this for both H10N1 and H10N6 AIVs as well as high mortality in mice.…”
Section: Discussionmentioning
confidence: 85%
“…Two North American LPAI H7N1 viruses isolated during wild bird surveillance efforts were found to cause severe disease in the DBA/2 mouse model [ 16 ], a strain with differential susceptibility to influenza viruses compared with the BALB/c model employed here [ 43 ]. Eurasian-lineage LPAI H7N1 viruses were found to replicate in mice and were capable of severe disease depending on the virus strain and mouse species employed [ 44 , 45 ]. Additionally, an HPAI H7N1 Eurasian-lineage virus was capable of causing severe disease in ferrets and exhibited limited transmission in a direct contact setting; this virus was capable of supporting an airborne transmissible phenotype following serial passage in ferrets [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The H7 subtype AIV has spread worldwide and has been detected in China (Wu et al, ), the United States (Olsen et al, ), Korea (Lee et al, ), Bangladesh (El‐Shesheny et al, ), Australia (Scott et al, ), Cambodia (Horwood et al, ) and Belgium (Van Borm et al, ). The pathogenic H7 subtype AIV changed from low pathogenicity in birds to high pathogenicity in both humans and birds (Dhingra et al, ).…”
Section: Discussionmentioning
confidence: 99%